Multiple recurrences after endoscopic removal of common bile duct stones: A retrospective analysis of 976 cases. Issue 8 (20th March 2019) - Kawaji, Yuki; Isayama, Hiroyuki; Nakai, Yousuke; Saito, Kei; Sato, Tatsuya; Hakuta, Ryunosuke; Saito, Tomotaka; Takahara, Naminatsu; Mizuno, Suguru; Kogure, Hirofumi; Matsubara, Saburo; Tada, Minoru; et al.
Abstract: Background and Aim: Recurrences after endoscopic treatment of common bile duct stones (CBDS) are common. The aims of this study were to identify risk factors for recurrences of CBDS and to evaluate the effect of interventions for prevention of further recurrences. Methods: A total of 976 patients who underwent endoscopic treatment of CBDS were retrospectively studied. Risk factors for single and multiple recurrent CBDS were evaluated using a Cox hazard regression model. The incidences of further recurrences were evaluated according to the additional interventions. Results: The mean age was 69.3 years, and 39.3% were female. Endoscopic papillary balloon dilation, endoscopic sphincterotomy, and endoscopic papillary large balloon dilation were performed in 858, 77, and 41 patients, respectively. The rates of one or more recurrence and multiple recurrences of CBDS were 12.4% and 2.7%, respectively. In the multivariate analyses, the significant risk factors were the bile duct size (hazard ratio [HR] 1.07, P = 0.012), gallbladder left in situ with stones (HR 1.91, P = 0.046), and pneumobilia after treatment (HR 2.10, P = 0.047) for single recurrence and the number of stones at the first recurrence (HR 1.16, P = 0.021) for multiple recurrences. In five out of nine cases with multiple recurrences, further recurrence was not observed after additional sphincteroplasty in addition to cholecystectomy. Conclusions: The incidence of multiple recurrences was not uncommon after the first recurrence of CBDS.